A prospective study of symptoms and neurocognitive outcomes in youth with concussion vs orthopaedic injuries. - Rieger, Brian P.; Lewandowski, Lawrence J.; Callahan, James M.; Spenceley, Laura; Truckenmiller, Adrea; Gathje, Rebecca; Miller, Laura A. (Brain Injury, 2013)
Background: This study examined symptom reports and neurocognitive outcomes in children (8-17 years) with mild traumatic brain injury (mTBI) or orthopaedic injury (OI). Method: Children and parents were initially assessed upon presentation in the Emergency Department of a local hospital and again at 3 months. Children completed the Immediate Post-Concussion Assessment and Cognitive Testing battery (ImPACT) and parents completed the Behavior Rating Inventory of Executive Function (BRIEF). The Peabody Picture Vocabulary Test, 3rd edition (PPVT-III) was completed by the children at the 3-month assessment. Results: Children with mTBI reported more symptoms than the OI group initially, but did not differ from the OI group at 3 months. Both groups reported a higher than expected number of symptoms at 3 months. On the ImPACT, children with mTBI performed significantly worse than the OI on a visual memory test at both assessments. The OI group had higher levels of parent-reported executive dysfunction on the BRIEF at initial and 3-month assessments. Discussion: As expected, more post-concussion symptoms were initially reported by children and adolescents with mTBI vs orthopaedic injury, but there was no difference at 3 months. The BRIEF and ImPACT cognitive measures did not differentiate concussed subjects from controls, with the exception of concussed subjects' lower performance on a visual memory test at both initial assessment and at 3 months.